2012
DOI: 10.1097/mej.0b013e32834bbd93
|View full text |Cite
|
Sign up to set email alerts
|

The First View Concept

Abstract: The number of patients seeking treatment in emergency departments is rising, although many governments are seeking to reduce expenditure on health. Emergency departments must achieve more with the same resources or perform the same functions with fewer resources. Patients demand higher emergency clinical care quality, with low waiting times viewed as a key quality criterion by many patients. The objective of this study was to create an improved working system in emergency departments that cuts patient waiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition, while multiple studies and governing bodies, including the Institute of Medicine (IOM), 20 have suggested increased use of systems engineering and improvement science to combat this growing problem, only recently has the emergency medicine literature started to demonstrate the successes that many similarly complex industries discovered long ago. 21 24 Still, there remains significant opportunity to refine the use and application of these tools across EDs in an effort to continue to optimize care, especially with respect to streamlining processes and improving throughput, and thus creating much needed capacity. 25 30 For example, Lean methodologies, originally designed for use in process improvement in the manufacturing industry, represent one potential tool for use in improving systems of care and throughput in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while multiple studies and governing bodies, including the Institute of Medicine (IOM), 20 have suggested increased use of systems engineering and improvement science to combat this growing problem, only recently has the emergency medicine literature started to demonstrate the successes that many similarly complex industries discovered long ago. 21 24 Still, there remains significant opportunity to refine the use and application of these tools across EDs in an effort to continue to optimize care, especially with respect to streamlining processes and improving throughput, and thus creating much needed capacity. 25 30 For example, Lean methodologies, originally designed for use in process improvement in the manufacturing industry, represent one potential tool for use in improving systems of care and throughput in the ED.…”
Section: Introductionmentioning
confidence: 99%
“…The nurse-to-patient ratio ranges from 1:3 to 1:5. Caregivers see patients on a first-view [ 22 ], on-site, 24/7 basis. Whether they work 8-, 10-, or 12-hour shifts, they all work in the same area, have access to the same patient volume, and see the same patient complaints.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in the ED of the Katharinenhospital Stuttgart which is an adult tertiary referral and major trauma hospital in South-Western Germany It provides interdisciplinary emergency treatment for 100-120 patients per day. The center adopts the First View Concept 14 , in which an emergency registrar/consultant sees each patient in an interdisciplinary approach. The center has 23 treatment rooms with central monitoring, one resuscitation rooms, one wound and one plaster room.…”
Section: Methodsmentioning
confidence: 99%